Pengaruh Waktu Dan Konsentrasi Katalis Terhadap Kualitas Pulp Dari Batang Sawit Bebas Pati Pada Proses Organosolv - Ahria Maulisa; Zulfansyah Zulfansyah; Hari Rionaldo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Oil palm trunk is a solid agricultural waste that has not been optimally utilized. One of the uses of oil palm trunk is by relieve starch to be used as a raw material for making pulp. This experiment was intended to study the possibility of using starch-free oil palm trunk as the alternative raw material in the pulp industry. The experiment was carried out in batch on a laboratory scale. The catalyst (HCl) concentration were studied at 0%, 0,05%, 0,10%, 0,15% 0,20%-weight at different reaction times (0, 5, 10, 15, 20, 30, 45, 60, 90, 120, and 180) minutes using 85%-weight formic acid as the solvent, and liquid to solid ratio of 15:1. From the research that has been done, it was found that the best conditions for pulp cooking with the organosolv process, namely with a catalyst concentration of 0.2% with a reaction time of 60 minutes, producing pulp with 93.17% alpha cellulose content, 37.05% yield, while the lowest lignin content. obtained at a concentration of 0.1% with a reaction time of 60 minutes that is equal to 12%.Keywords: alpha cellulose, lignin, formic acid, orgnosolv, starch-free oil palm trunk